La importancia de la terminología jurídica en la interpretación en los Servicios Públicos: Un caso empírico de interpretación social español-francés - Cobos López, Ingrid; Ruiz Mezcua, Aurora (Anales de Filología Francesa, 2010)
The aim of this article is to highlight the importance of using the accurate terminology when working as an interpreter for the public services, especially when dealing with Court or Police station matters. For this reason, its teaching and understanding is vital for a quality translator and interpreter training. This article provides a reflection on the importance of juridical terminology and a text typology analysis. Besides, we study a form based on our own experience as community interpreters in Córdoba´s Police station. We extract specific terminology and translation problems. Finally, we compile a glossary, and we include a translation proposal of the above mentioned document into French.